1993
DOI: 10.1093/hmg/2.7.947
|View full text |Cite
|
Sign up to set email alerts
|

The genes for X-linked ocular albinism (OA1) and microphthalmia with linear skin defects (MLS): cloning and characterization of the critical regions

Abstract: We have used cell lines from patients with deletions and translocations involving the Xp22 region to map the genes for two X-linked disorders, ocular albinism type 1 (OA1) and microphthalmia with linear skin defects (MLS). Using existing and newly isolated DNA markers, the map position within Xp22 of key patient breakpoints, defining the boundaries of the genomic regions involved in these disorders (the critical regions), has been precisely determined. A 2.6 Mb yeast artificial chromosome (YAC) contig, spannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…chorioretinal abnormalities, microphthal mia, callosal agenesis, seizures, and mental retardation) with the microphthalmia with linear skin defects syn drome [20,21]. Similar to Aicardi syndrome, this disease is X-linked and the MLS chromosomal locus has been specifically mapped to Xpter to Xp22 [22,23], The puta- five gene affected in MLS has been cloned and is homolo gous to mitochondrial holocytochrome c-type synthetases identified in other organisms [24], Schaefer et al [24] per formed a mutational analysis of the human holocyto chrome c-type synthetase (HCCS) gene in lymphoblasts derived from 7 Aicardi syndrome patients. No evidence of gene rearrangements or mutations was seen.…”
Section: Discussionmentioning
confidence: 99%
“…chorioretinal abnormalities, microphthal mia, callosal agenesis, seizures, and mental retardation) with the microphthalmia with linear skin defects syn drome [20,21]. Similar to Aicardi syndrome, this disease is X-linked and the MLS chromosomal locus has been specifically mapped to Xpter to Xp22 [22,23], The puta- five gene affected in MLS has been cloned and is homolo gous to mitochondrial holocytochrome c-type synthetases identified in other organisms [24], Schaefer et al [24] per formed a mutational analysis of the human holocyto chrome c-type synthetase (HCCS) gene in lymphoblasts derived from 7 Aicardi syndrome patients. No evidence of gene rearrangements or mutations was seen.…”
Section: Discussionmentioning
confidence: 99%
“…To map the putative inversion breakpoint in Xp22.3 more precisely, we performed FISH analysis with YAC clone 225H10, which contains part of the previously defined MLS critical region (Wapenaar et al, 1993) and which has been found to be deleted in three patients with MLS syndrome (Lindsay et al, 1994). In the majority of the 38 metaphases analyzed with YAC 225H10, we observed one distinct signal on the short arm of the X chromosome (Fig.…”
Section: Conventional and Molecular Cytogenetic Studiesmentioning
confidence: 92%
“…By mapping the breakpoints of MLS patients, an F 570-kb minimal region of monosomy has been identified in Xp22.3 (Wapenaar et al, 1993;, distal to AMELX (amelogenin) (Lagerstrom et al, 1991), and cloned into overlapping cosmids (Cox et al, 1998). Three genes have been mapped and characterized in the critical deletion interval for MLS: MID1 (midline-1) mutated in the X-linked Opitz G/BBB syndrome (Quaderi et al, 1997), HCCS which encodes the human holocytochrome c-type synthetase (Schaefer et al, 1996), and ARH-GAP6 encoding a Rho GTPase activating protein (Schaefer et al, 1997).…”
Section: Copyright © 2002 S Karger Ag Baselmentioning
confidence: 99%
“…6,8,9 Based on the molecular characterisation of the chromosomal abnormalities in MLS patients, a 0.6 Mb genomic region was reported to contain all or part of the disease gene(s). 10,11 Here we report the near-complete and fully annotated cosmid contig covering approximately 1.7 Mb distal to Amelogenin and encompassing the critical region for MLS. Over 40 new polymorphic repeat markers have been developed and these, together with all relevant anchor STS markers from the larger linkage and YAC-based physical maps.…”
Section: Introductionmentioning
confidence: 99%